865 Launching the ethiopia health care quality initiative: interim results and initial lessons learned. (21st November 2017) - Magge, Hema; Kiflie, Abiyou; Mulissa, Zewdie; Abate, Mehiret; Biadgo, Abera; Bitewulign, Befikadu; Alemu, Hareg; Brooks, Kathryn; Mohammed, Hassen; Burssa, Daniel
Abstract : Background: Since 2013, IHI has worked with the Ethiopian Federal Ministry of Health (FMoH) to leverage QI methodologies to accelerate progress of the FMoH in maternal newborn health (MNH), and build a culture of quality in the health system. Objectives: Understand initial successes, challenges, and results of a multi-faceted strategy aimed at institutionalising QI and improving MNH outcomes in a resource-limited setting. Methods: Three collaboratives launched in three regions of Ethiopia April-September 2016. We report programmatic and core clinical indicators after LS1 (October 2016-June 2017). Monthly means of program process measures were extracted from routine monitoring tools. Control charts for core HMIS-derived indicators use baseline data (July 2015-August 2016) to set control limits and extend forward. Bundle implementation is displayed using run charts. Results: Currently, LS3 has been completed, and 57 health care workers have been trained in QI along with 83 manager-level staff. 20 QI teams have conducted 506 PDSA cycles. Sixteen (80%) teams have reported signals of improvement in bundle adherence by LS2. Aggregate control charts demonstrate initial improvement in data quality in 4-visit ANC, PNC within 48 hours of delivery, and skilled delivery as seen by an initial apparent performance drop. ANC coverage, PNC coverage, percent of women tested for syphilis during first ANC visit, and clinical bundles continued with signals of improved care quality with upward trend (see charts). Conclusions: Initial results are promising regarding program delivery and indicate high levels of facility-level QI activities, as well as initial signals of improved data and service quality in key maternal newborn health services.